The Development of Animal Physiology Textbook Based on Higher Order Thinking Skills for Biology Department Students - Indra Jaya Purba; Melva Silitonga; Idramsa Idramsa (Jurnal Pendidikan Biologi, 2022)
The students’ higher order thinking skills were still low due to the learning system, such as the use of textbooks that have not led to an increase in higher order thinking skills. The availability of updated textbooks based on higher order thinking skills was needed in the university. The aim of this study was to develop a textbook based on higher order thinking skills on animal physiology course. The development model used in this study was the Thiagarajan (4D) development model which consisted of define, design, development and dissemination. However, the research stage carried out was only up to development. The developed textbook was validated based on three criterias, namely material, language and design. The developed textbook was also tested to students who have taken animal physiology course and obtained the students’ response. The result of validation by material expert was 86 in the category of “Very Good”, language expert was 88 in the category of “Very Good”, design expert was 87 in the category of “Very Good” and students’ response according to individually, small group and limited group were 86, 89 and 89 respectively. The whole students’ responses were categorized as “Very Good”. It can be concluded that the product can be used as a textbook in animal physiology course. This study is useful as a learning source for students and an alternative teaching material for lecturers, as well as improving the quality of animal physiology learning.